The Covid-19 Pandemic in Indonesia: Children as Children First, Child Refugees Second? - Puspita, Natalia Yeti (JUSTITIA JURNAL HUKUM, 2023)
Indonesia is often a transit country for refugees, even though Indonesia is not ratified the 1951 Refugee Convention and the 1967 Refugee Protocol. The Covid-19 pandemic has made it even more challenging to fulfil human rights guarantees for child refugees in Indonesia. Child refugees and refugees who were not accompanied by adults are the group most vulnerable to human rights violations.Based on this, this paper will analyze the legal protection for child refugees in Indonesia during the Covid-19 pandemic. This article is the result of normative legal researchwhichemphasizes secondary data. The data was obtained through library research.The legal protection for handling refugees, especially child refugees in Indonesia and during the Covid-19 pandemic, is based on the principle of non-refoulment, the principle of non-discrimination and the principle of the best interests of child.Keywords: Legal Protection, Child Refugees, Indonesia, Covid-19 Pandemic.